Bit Rate Maximising Per-Tone Equalisation with Adaptive Implementation for DMT-Based Systems. (9th November 2009) - Sitjongsataporn, Suchada; Yuvapoositanon, Peerapol
Abstract : We present a bit rate maximising per-tone equalisation (BM-PTEQ) cost function that is based on an exact subchannel SNR as a function of per-tone equaliser in discrete multitone (DMT) systems. We then introduce the proposed BM-PTEQ criterion whose derivation for solution is shown to inherit from the methodology of the existing bit rate maximising time-domain equalisation (BM-TEQ). By solving a nonlinear BM-PTEQ cost function, an adaptive BM-PTEQ approach based on a recursive Levenberg-Marquardt (RLM) algorithm is presented with the adaptive inverse square-root (iQR) algorithm for DMT-based systems. Simulation results confirm that the performance of the proposed adaptive iQR RLM-based BM-PTEQ converges close to the performance of the proposed BM-PTEQ. Moreover, the performance of both these proposed BM-PTEQ algorithms is improved as compared with the BM-TEQ.